KONSTRUKSI WACANA CHILDFREE PADA PUS NON KB KAMPUNG KB DI DESA JATISARI PAKISAJI MALANG - Singgih Susilo (Jurnal Environmental Science, 2022)
ABSTRACTMarriage without the presence of a child is a new reality in Indonesian society. The development of the discourse began with several influencers who decided to get married but did not have children. In the end, the event was widely discussed until it became a lifestyle in the community, especially age couples in Jatisari village. This study seeks to reveal how the construction of Childfree discourse is developing in the community, especially marginal age couples in Jatisari Village, Pakisaji Malang. The method in this study uses a qualitative approach using a phenomenological approach that focuses on the social construction of Luckman and Berger. Determining the research subjects as many as seven people using a purposive technique that has several criteria. Data analysis was carried out using a model developed by Huberman which included reduction, data presentation, and conclusions. The results of this study indicate that two Childfree constructs are different from the dominant discourse. First, Childfree was constructed as an effort to thin out children. Second, Childfree was constructed as an effort to increase welfare without the presence of a child.